Tumour-Associated Transcripts and EGFR Deletion Variants in Colorectal Cancer in Primary Tumour, Metastases and Circulating Tumour Cells - Silke Lankiewicz; Eva Rother; Silke Zimmermann; Christiane Hollmann; Firouzeh Korangy; Tim F. Greten (Cellular Oncology)
The clinical relevance of circulating tumour cells (CTC) in peripheral blood of patients with colorectal cancer (CRC) has been described as an independent prognostic factor useful to monitor drug effects and clinical status. The aim of the present study was to compare the epidermal growth factor receptor (EGFR) status of primary tumour, related metastases and CTC of patients with CRC. Therefore, in addition to EGFR, the tumour-associated transcripts gastrointestinal tumour-associated antigen 733-2 (GA733-2) and carcinoembryonic antigen (CEA) were analyzed in a multiplex RT-PCR to characterize CTC. 55% patients were positive for CTC. EGFR expression was detected in 18% of these patients. EGFR was expressed more frequently in metastatic and primary tumour tissues as revealed by immunohistochemistry. Besides, detailed expression profiling of EGFR variants in various colorectal and glioma cell lines has been performed to generate positive controls, resulting in the discovery of two new transcript deletion variations (cEX12_15del, cEX12_14del) located on the extracellular domain of the EGFR.